Matching disruptive innovation paths with entrepreneurial networks: a new perspective on startups' growth with Chinese evidence - Weizhen Yu; Shuanping Dai; Feng Liu; Yi Yang (Asian Business & Management, 2022)
This study examines the impacts of entrepreneurial networks on startups' performance with a sample of 618 startups in China's Yangtze River Delta region, focusing on matching disruptive innovation paths with network types. The results indicate that entrepreneurial networks (both heterogeneous and homogeneous) are meaningful for startups' growth performance. The study finds that startups exploring low-end disruption may benefit more from heterogeneous peers and avoid networking with an abundance of homogeneous peers. However, if exploring new markets, both types of networks could provide positive impacts. The asymmetric mediation effects of disruptive innovation paths highlight the core of leveraging entrepreneurial networks, whether homogeneous or heterogeneous, is to activate network resources with proper disruption paths.
Keywords: 650; Startups' growth; Entrepreneurial networks; Disruptive innovation